2022
DOI: 10.3390/nu14245261
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Small Intestinal Bacterial Overgrowth in Patients with Non-Alcoholic Liver Diseases: NAFLD, NASH, Fibrosis, Cirrhosis—A Systematic Review, Meta-Analysis and Meta-Regression

Abstract: Bacterial overgrowth in the small intestine (SIBO) is a pathological growth of the intestinal microbiota in the small intestine that causes clinical symptoms and can lead to digestive and absorption disorders. There is increasing evidence that people with NAFLD have a distinct gut microflora profile as well metabolome changes compared to people without NAFLD. Thorough analysis of observational and RCT studies in the current databases (EMBASE, Web of Science, PubMed, Cinahl, Clinical Trials) was conducted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…The increase in small intestinal permeability and small intestinal microbial overgrowth may promote hepatic lipid accumulation and the development of inflammation. [31,32] Jang et al found that the small intestine protects the liver from fructose induced steatosis. [33] However, the important role of the small intestinal microbes in suppressing liver inflammation remains to be revealed.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in small intestinal permeability and small intestinal microbial overgrowth may promote hepatic lipid accumulation and the development of inflammation. [31,32] Jang et al found that the small intestine protects the liver from fructose induced steatosis. [33] However, the important role of the small intestinal microbes in suppressing liver inflammation remains to be revealed.…”
Section: Discussionmentioning
confidence: 99%
“…The odds for small intestinal bacterial overgrowth (SIBO) prevalence in patients with FD was significantly higher as compared to controls [4. [11,12] including systemic sclerosis [13], chronic liver disease [14] and Parkinson's disease. Three systematic reviews and meta-analyses have confirmed increased prevalence of SIBO in patients with chronic liver disease [14][15][16], irrespective of the aetiology of liver disease [15] and SIBO prevalence was significantly increased in patients with decompensated cirrhosis as compared to those with compensated cirrhosis [16], (50.5% vs. 31.2%; P < 0.001). Similarly, SIBO prevalence in is increased in patients with Parkinson's disease as compared to controls (OR ¼ 5.22, 95% CI 3.33-8.…”
Section: Small Intestinal Dysbiosismentioning
confidence: 94%
“…Furthermore SIBO has been linked to several extra-intestinal disorders [11,12] including systemic sclerosis [13], chronic liver disease [14] and Parkinson's disease. Three systematic reviews and meta-analyses have confirmed increased prevalence of SIBO in patients with chronic liver disease [14–16], irrespective of the aetiology of liver disease [15] and SIBO prevalence was significantly increased in patients with decompensated cirrhosis as compared to those with compensated cirrhosis [16], (50.5% vs. 31.2%; P < 0.001). Similarly, SIBO prevalence in is increased in patients with Parkinson's disease as compared to controls (OR = 5.22, 95% CI 3.33–8.19), A recent meta-analysis [13], reported a 10-fold increased prevalence of SIBO in patients with systemic sclerosis as compared to controls, (OR = 9.6, 95% CI 5.6–16.5, P = 0.0001), with diarrhoea (OR = 5.9, 95% CI 2.9–16.0, P = 0.001) being associated with SIBO in patients with systemic sclerosis.…”
Section: Defining the Termsmentioning
confidence: 94%
“…( 99 ) Finally, we considered, but did not include, studies in patient populations rarely encountered in routine clinical practice, studies with significant heterogeneity, or studies where the reported association of SIBO was potentially confounded by additional variables (such as lifestyle, diet, and concurrent diseases) ( 100 109 ). Although a newer systematic review/meta-analysis on liver disease was available, the results of this analysis pooled all test modalities, and thus, we selected an older systematic review as the reference for SIBO prevalence for liver disease ( 110 ).…”
Section: Methodsmentioning
confidence: 99%